Borrowing Capacity and Financial Decisions of Low‐to‐Moderate Income First‐Time Homebuyers. Issue 3 (30th October 2013) - MOULTON, STEPHANIE; LOIBL, CÄZILIA; SAMAK, ANYA; MICHAEL COLLINS, J.
<x xml:space="preserve">Abstract</x> This study documents the extent to which first‐time homebuyers seeking a mortgage accurately estimate their borrowing capacity and how this is associated with their decisions regarding mortgage debt and the take‐up of a free offer of financial coaching. We find that consumers who underestimate their nonmortgage debt (31.5% of the sample) also take out larger mortgages relative to income. Consumers who underestimate or overestimate their total debt as well as their monthly debt payments are more likely to accept the offer of financial coaching. Moreover, overconfidence in financial matters reduces the take‐up of financial coaching. These biases in perceived financial status appear to be systematically related to behavior among a group of relatively inexperienced consumers. These findings suggest that efforts to extend homeownership may need to include debiasing mechanisms to help less informed consumers accurately assess their current debt levels and ability to make ongoing mortgage payments.